(untitled) (Movimenta (ISSN 1984-4298), 2021)
Burnout syndrome (SB) is an emotional disorder with symptoms of stress, extreme exhaustion and physical exhaustion, the main cause of the syndrome being excessive work. Burnout is common in professionals who work daily under constant pressure, such as police officers, doctors, nurses, teachers, journalists and physiotherapists. The aim of this study was to investigate the presence of Burnout Syndrome in police officers from ROTAM (Metropolitan Tactical Ostensive Rounds), assess the level of quality of life and associate it with BS and sociodemographic profile. This is a cross-sectional, descriptive study with police officers assigned to the ROTAM battalion in Goiânia, which involves a systematic collection of information through the sociodemographic profile, Maslach Burnout Inventory (MBI) and WHOQOL-bref. The MBI results showed that the majority of participating police officers did not show significant symptoms of SB. The survey showed that 81.3% of officers in ROTAM have a low risk of developing burnout syndrome, 13.9% show trends and 4.8% are indicative of SB. It was found that the quality of life of police officers in ROTAM is considered good, with a final average score of 77, with a higher score in the psychological domain of 80.28 and a lower score in the environmental domain of 69.72.